2017
DOI: 10.1186/s13293-017-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific phenotypes of hyperthyroidism and hypothyroidism in aged mice

Abstract: BackgroundSex and age play a role in the prevalence of thyroid dysfunction (TD), but their interrelationship for manifestation of hyper- and hypothyroidism is still not well understood. Using a murine model, we asked whether sex impacts the phenotypes of hyper- and hypothyroidism at two life stages.MethodsHyper- and hypothyroidism were induced by i.p. T4 or MMI/ClO4-/LoI treatment over 7 weeks in 12- and 20-months-old female and male C57BL/6N mice. Control animals underwent PBS treatment (n = 7–11 animals/sex/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
0
29
0
2
Order By: Relevance
“…A shortcoming of our study is that we only determined the age effect at two time points (basal and 12 hours after acute T 4 challenge), and that we cannot extrapolate on long-term effects on the organism. However, in previous studies we have observed age-dependent differences on phenotypic traits of chronic hyper-and hypothyroidism in mice and think that they are of physiological relevance (26,27). A strength of our study is the characterization of very old mice of 23 months of age in a direct comparison to 3 months old mice.…”
Section: Thyroidmentioning
confidence: 81%
“…A shortcoming of our study is that we only determined the age effect at two time points (basal and 12 hours after acute T 4 challenge), and that we cannot extrapolate on long-term effects on the organism. However, in previous studies we have observed age-dependent differences on phenotypic traits of chronic hyper-and hypothyroidism in mice and think that they are of physiological relevance (26,27). A strength of our study is the characterization of very old mice of 23 months of age in a direct comparison to 3 months old mice.…”
Section: Thyroidmentioning
confidence: 81%
“…In contrast, no weight difference was seen in hypothyroid female iTGa s KO mice compared with controls despite a similar degree of hypothyroidism. Unlike in humans, where weight gain is a classic symptom of hypothyroidism, weight loss has been reported when hypothyroidism is induced pharmacologically in rodents (44,45). The reason for the different adaptation of body weight in hypothyroidism between male and female iTGa s KO mice remains unclear, but it may reflect, for example, sex-specific differences in tissue deiodinase activities, thyroid hormone uptake, and/or energy expenditure, as suggested previously (46).…”
Section: Discussionmentioning
confidence: 94%
“…One explanation is that the proteins we observed altered by TH status are predominantly involved in myocardial substrate utilization as opposed to structural or hypertrophic changes. Supporting this rationale, previous work in our lab showed TH treated aged male mouse heart experienced signi cant alterations in substrate utilization with fatty acids, but exhibited limited or unchanged cardiac functions compared to baseline or aged untreated [30,32,33]. Thus, we would need to do speci c studies on cardiac substrate utilization for fatty acids to de ne these sex-differences.…”
Section: Discussionmentioning
confidence: 90%
“…A prior investigation [30] reported that sex modulates TH action in both 12 and 20 months old C5/BL/7 mice. Those investigators studied effects of thyroid state on multiple systemic parameters such as body temperature and weight, as well as muscle strength and locomotor coordination.…”
Section: Discussionmentioning
confidence: 94%